Teaching Intermediate Technology Education in Newfoundland and Labrador ... - Gill, David (Graduate Studies, 2017)
The purpose of this study was to explore the teaching of intermediate technology education within the Newfoundland and Labrador context. As there were no empirical investigations prior to this study, this investigation was important in creating new knowledge that can be utilized by multiple groups that lay claim on intermediate technology in the province. Further, this study firmly placed Newfoundland and Labrador’s implementation of intermediate technology education within the international scholarly community. As such, it has addressed key points concerning teacher experience and belief, professional development, leadership, and curricular marginalization. The main research question for this study focused on what factors support or hinder the capability and capacity of intermediate technology education teachers in Newfoundland and Labrador. From this question, a qualitative exploratory case study design was developed that used an online teacher questionnaire, semi-structured teacher and administrator ...